Produksi dan Karakteristik Biji Lamtoro (Leucaena leucocephala) di Lahan Kering Bukit Jimbaran - Tegar Rahman Maulana; Anak Agung Ayu Sri Trisnadewi; Magna Anuraga Putra Duarsa (Pastura: Jurnal Ilmu Tumbuhan Pakan Ternak, 2025)
Animal husbandry plays a crucial role in the Indonesian economy, with livestock productivity heavily dependent on the availability of forage feed. Leucaena leucocephala seeds have an important role in plant breeding to meet forage feed needs. This study aims to determine the production and characteristics of Leucaena leucocephala seeds on dry land. The research was conducted at the Seedling Farm of the Facultyof Animal Husbandry, Udayana University, Bukit Jimbaran, Badung, from December 2023 to March 2024. Data were collected through the field survey method with the transect method in 55 m quadrat plots in five locations as replicates. Observations were made in two collections, in December 2023 and March 2024. The results showed that seed production and characteristics in the first collection were higher than in thesecond collection. The average seed production in December 2023 reached 1,586.78 seeds and decreased to 988.60 seeds in March 2024, with an average annual production of 5,150.76 seeds. Seed weight reached 0.618 tons ha-1 in December and decreased to 0.592 tons ha-1 in March. A decline in seed characteristics was also observed in the number of bunches per plant (from 20.31 to 15.69), number of pods per bunch (22.63 to 17.05), and number of seeds per pod (23.23 to 18.95). This decrease indicates that the production and seed characteristics of Leucaena leucocephala in drylands tend to decrease in the second collection. ABSTRAK Peternakan memiliki peranan penting dalam perekonomian Indonesia, dengan produktivitas ternak yang bergantung pada ketersediaan pakan hijauan. Biji lamtoro (Leucaena leucocephala) berperan penting dalam perkembangbiakan tanaman untuk memenuhi kebutuhan hijauan pakan. Penelitian ini bertujuan untuk mengetahui produksi dan karakteristik biji lamtoro di lahan kering. Penelitian dilaksanakan di Kebun Bibit Fakultas Peternakan Universitas Udayana, Bukit Jimbaran, Badung, dari Desember 2023 hingga Maret 2024. Data diambil melalui metode survei lapangan dengan metode transect pada kuadrat petak berukuran 55 m di lima lokasi sebagai ulangan. Pengamatan dilakukan pada dua pengambilan yaitu pada Desember 2023 dan Maret 2024. Hasil menunjukkan bahwa produksi dan karakteristik biji pada pengambilan pertama lebih tinggi dibandingkan pengambilan kedua. Rata-rata produksi biji pada Desember 2023 mencapai 1.586,78 biji dan menurun menjadi 988,60 biji pada Maret 2024, dengan produksi tahunan rata-rata 5.150,76 biji. Berat biji mencapai 0,618 ton ha-1 pada Desember dan menurun menjadi 0,592 ton ha-1 pada Maret. Penurunan karakteristik biji juga terlihat pada jumlah tandan per tanaman (dari 20,31 menjadi 15,69), jumlah polong per tandan (22,63 menjadi 17,05), dan jumlah biji per polong (23,23 menjadi 18,95). Penurunan ini mengindikasikan bahwa produksi dan karakteristik biji lamtoro di lahan kering cenderung menurun pada pengambilan kedua.